Correlation of C-Reactive Protein (CRP) Levels with D-Dimer Levels in COVID-19 Patients - Choirunisa, Churiyyah Eka; Widhyasih, Retno Martini; Fajrunni’mah, Rizana (Poltekkes Kemenkes Jakarta III, 2023)
Coronavirus disease 2019 is caused by SARS-CoV-2 infection. COVID-19 causes increased levels of proinflammatory cytokines, so CRP and d-dimer levels in COVID-19 patients tend to increase. This study aimed to analyze the correlation between C-Reactive Protein (CRP) levels and D-dimer levels in COVID-19 patients. This research method is analytic observational by using cross-sectional secondary data. The population of this study were all COVID-19 inpatients at Budhi Asih Hospital, East Jakarta, with a sample of 338 patients and were taken by random sampling. The results of this study found that female and male COVID-19 patients had the same risk of being infected with female patients as much as 52,7% and male patients amounting to 47,3%. Most COVID-19 patients occurred at the age of ≥60 years, namely 32,2%. All patients, which is 100% patients had high CRP levels, with a mean of 76,06 mg/L. As for D-dimer levels, 47,9% of patients had normal D-dimer levels and 52,1% had high D-dimer levels with an average of 721,48 ng/mL. The results of the Spearman's correlation test obtained a p value = 0,000, so it can be seen that there is a correlation between C-Reactive Protein (CRP) levels and D-dimer levels in COVID-19 patients with a correlation strength of 0,300 (medium). An increase in CRP levels followed by an increase in D-dimer levels but evaluation of other laboratory examination parameters also needs to be considered.